Synthesis And Properties Of Highly Cross-Linked Polysiloxane For LED Encapsulant - Looi, Yien Tyng (2012)
The research focuses on the synthesis of two series of polysiloxane. The first series (S1) is hydrosilyl-terminated polydimethylsiloxane (HTP) that was cured with 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl cyclotetrasiloxane (D4V) and second series (S2) is the incorporation of octaphenylcyclotetrasiloxane (P4) into first series. The polymers of both series underwent thermal curing. UV curing was performed on the first series to improve the curing time as well as comparing their properties. The polysiloxanes product was a water clear gel form. The elastomeric feature of series S1 was dependent on the end-capper concentration, 1,1,3,3- tetramethyldisiloxane while series S2 was dependent on the amount of phenyl group of octaphenylcyclotetrasiloxane (P4) employed during its synthesis. FTIR and NMR was used to confirm the functional group of HTP and completion of the hydrosilylation reaction.